2022
DOI: 10.1590/fst.87322
|View full text |Cite|
|
Sign up to set email alerts
|

Stability and antioxidant activity of flavonoids from Lycium barbarum L. leaves during digestion in vivo

Abstract: It has been determined that Lycium barbarum L. leaves are a vital source of bioactive chemicals and have good potential for creating nutritious formulations. In this work, gavage injections of Lycium barbarum L. leaves flavonoids (LBLF) at various doses -50, 150, and 300 mg/kg BW -were administered to Sprague-Dawley (SD) rats. Four main LBLFs (rutin, chlorogenic acid, kaempferol, and quercetin) were assessed for stability and antioxidant activity in vivo. The findings demonstrated that within 4 h of the LBLF i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Studies have consistently shown us that nutrition plays a big part in many diseases (Ji et al, 2022), and a healthy life style can help prevent many metabolic diseases, such as diabetes (Chen et al, 2023;Fan et al, 2022;Zapata et al, 2022). Furthermore, some chronic diseases require special diets that should be monitored by your physician.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have consistently shown us that nutrition plays a big part in many diseases (Ji et al, 2022), and a healthy life style can help prevent many metabolic diseases, such as diabetes (Chen et al, 2023;Fan et al, 2022;Zapata et al, 2022). Furthermore, some chronic diseases require special diets that should be monitored by your physician.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Lycium barbarum leaves are rich in nutrients, including protein, minerals, nicotinic acid, polysaccharides, and flavonoids [ 15 , 16 ]. The leaves of Lycium barbarum are the main source of bioactive substances, with certain nutrients exceeding the contents found in the fruits [ 17 ]. Therefore, this suggests that the branches and leaves of Lycium barbarum (LBL) can serve as livestock forage.…”
Section: Introductionmentioning
confidence: 99%
“…It is based on the application of high-frequency sound waves between 20 and 100 kHz, generating a cavitation effect (Demirci et al, 2022;Xu et al, 2022). Several studies demonstrated its effectiveness as an emerging non-thermal technology during the extraction of phenolic compounds (Dadi et al, 2019;Dal Prá et al, 2015;Görgüç et al, 2022;Guandalini et al, 2019;Monteiro et al, 2022;Pradal et al, 2016), such as rutin, a flavanol characterised by its antioxidant capacity but whose bioavailability is low due to its low water solubility, poor chemical and metabolic stability, and limited membrane permeability (Fan et al, 2022;Zitha et al, 2022).…”
Section: Introductionmentioning
confidence: 99%